Synergistic bond strengthening in epoxy adhesives using polydopamine/MWCNT hybrids. (15th January 2016) - Subramanian, Alamelu Suriya; Tey, Ju Nie; Zhang, Liying; Ng, Bo Hui; Roy, Sunanda; Wei, Jun; Hu, Xiao 'Matthew'
Abstract: Polydopamine (PDA) was spontaneously coated on acid treated MWCNT or pristine MWCNT surface via oxidative polymerization. The effect of PDA modified MWCNT hybrids on the lap shear strength of epoxy/aluminum joints and the failure mechanisms were systematically investigated. The PDA/acid modified MWCNT hybrid at only 0.5 wt% led to a substantial increase in the lap shear strength in comparison to neat adhesive by more than 100%, whereas addition of PDA alone or acid treated MWCNT alone led only to marginal change or much less improvement in lap shear strength. PDA coated pristine MWCNT hybrid also caused a significant increase in bond strength but to a lesser extent. Further analysis of these findings suggests that the substantial bond strength increase is attributable to simultaneous improvement of the interfacial adhesion to the substrate and the cohesive strength of the adhesive. The mechanistic understanding of the adhesive properties in such hybrid nano-adhesive systems is significant as it may lead to new generation of adhesives for various applications. Graphical abstract: Highlights: Epoxy was reinforced with PDA/MWCNT-COOH nano-hybrids. 100% increase in lap shear strength was achieved with 0.5 wt% filler loading. Possible key mechanisms involved in adhesive/cohesive strengthening are explained.